The Polar Regions - Canada, Mark; NC DOCKS at The University of North Carolina at Pembroke (2013)
The America that Poe inhabited in the early nineteenth was deeply engaged in geographic exploration. Three years before Poe’s birth in 1809, Lewis and Clark returned from their expedition across the newly acquired Louisiana Territory. Over the next half century, while Poe was growing up, serving in the U.S. Army, editing magazines and penning his poetry and fiction, Americans surveyed the Atlantic and Pacific coasts, blazed the Oregon and Santa Fe trails, and launched expeditions to the South Pacific, the Antarctic, and the American West. Meanwhile, fellow writers such as Richard Henry Dana and Herman Melville described factual and fictional journeys to distant places. It should come as no surprise, then, that Poe exploited this ubiquitous theme of discovery in his literature. Tales such as “Manuscript Found in a Bottle,” “The Unparalleled Adventure of One Hans Pfaall,” and The Narrative of Arthur Gordon Pym are replete with journeys, discoveries, and various exotic locales. For Poe’s fictional explorers, however, the real ultima Thule lay not in the South Seas or the South Pole, but in their own minds.